Stuart Lowe. Urban social movements : the city after Castells. Nueva York : St. Martin’s Press, 1986. 221 p. - Ramírez Sáiz, Juan Manuel (Estudios Demográficos y Urbanos, 1988)
STUARTLOWE: Urban Social Movements. The City after Castells, St. Martin's Press, Nueva York, 1986.